Решите уравнение ( 2х -1 ) ( 4х^2+2х+1)=23+4х (2х^2-3)

Решите уравнение ( 2х -1 ) ( 4х^2+2х+1)=23+4х (2х^2-3)

  • На фотке решение. Ответ: х=2
Решите уравнение ( 2х -1 ) ( 4х^2+2х+1)=23+4х (2х^2-3)

  • (2x-1)(4x +2x +1) =23 +4x(2x -3) ;
    (2x) -1 =23 +8x -12x ;
    8x - 1 =23 +8x -12x ;
    12x =24 ;
    x=2 .
  • Понравилась статья? Поделиться с друзьями:
    Добавить комментарий

    + 20 = 24

    ;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!: